2015
DOI: 10.1039/c5ra06591g
|View full text |Cite
|
Sign up to set email alerts
|

Anthracene-based ferrocenylselenoethers: syntheses, crystal structures, Cu(i) complexes and sensing property

Abstract: Three novel anthracene-based ferrocenylselenoethers, 1,5-diselena-3-(anthracen-9 0 -ylmethyl)- [5] ferrocenophane (L3), 1,3-bis(ferrocenylseleno)-2-(anthracen-9 0 -ylmethyl)propane (L4) and N,N-bis[2-(ferrocenylselena)ethyl]-N-(anthracen-9 0 -ylmethyl)amine (L5) and their Cu(I) complexes, [Cu 2 Br 2 (L2) 2 ] (L2 ¼ 1,1 0 -bis[2-(anthracen-9 0 -yloxy)-ethylseleno]ferrocene) (1), [Cu 2 I 2 (L2) 2 ] (2), [Cu 2 I 2 (L3) 2 ]$1.25CH 2 Cl 2 (3) and[Cu 4 I 4 (L5) 2 ]$CH 2 Cl 2 (4), have been prepared and structurally c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 47 publications
3
7
1
Order By: Relevance
“…The half-wave potentials for oxidation of the ferrocene moiety of L1 – L5 are all more negative than those of B1 – B5 , which means the ferrocene moiety is easier to oxidize after the incorporation of the DA unit. It is not surprising to find that the ferrocene moiety in the ferrocenophane L5 is easier to oxidize than that of the acyclic analogues, which is in agreement with our previous studies . Studies have shown that the lower half -wave potential for oxidation of the ferrocene moiety is related to better anticancer activity. , The oxidation of the ferrocene moiety can induce the catechol group to form reactive o -quinone products, which have much greater advantages in inhibiting the thioredoxin reductases, the key targets in anticancer drug action mechanisms…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The half-wave potentials for oxidation of the ferrocene moiety of L1 – L5 are all more negative than those of B1 – B5 , which means the ferrocene moiety is easier to oxidize after the incorporation of the DA unit. It is not surprising to find that the ferrocene moiety in the ferrocenophane L5 is easier to oxidize than that of the acyclic analogues, which is in agreement with our previous studies . Studies have shown that the lower half -wave potential for oxidation of the ferrocene moiety is related to better anticancer activity. , The oxidation of the ferrocene moiety can induce the catechol group to form reactive o -quinone products, which have much greater advantages in inhibiting the thioredoxin reductases, the key targets in anticancer drug action mechanisms…”
Section: Resultssupporting
confidence: 89%
“…Our continued interest in the study of ferrocenyl selenoethers led us to investigate their potential biomedical properties . Dopamine ( DA ) as a kind of neurotransmitter, has been reported to modulate tumor angiogenesis and immunity by inhibiting VEGF .…”
Section: Introductionmentioning
confidence: 99%
“…19,20 Our group has recently obtained four new copper(I) clusters built from ferrocenylseleno-anthracenes, which are dimers with a rhomboidal Cu 2 X 2 core or 1D loop chain polymers with a distorted cubane Cu 4 I 4 core. 21 No neutral tellurium-based ones have been synthesized until now. The structure and characteristics of CuX-Te/Se clusters will be the subject of intense research effort for understanding the interaction of Cu(I)-Te/Se in chalcogeno-complexes which have shown potential biological activities.…”
Section: Introductionmentioning
confidence: 99%
“…[64][65][66][67] Several reports have shown that Cu 2+ can oxidize the ferrocene unit into ferrocenium, Cu 2+ is then reduced to non-quenching Cu + because of its d 10 electron configuration. 26,64,65 In the field of NLO studies, the ferrocene unit mainly behaved as an electron donor in the charge transfer process, and the NLO properties of ferrocenyl derivatives can be readily and reversibly switched via the Fe III/II redox couple. [67][68][69][70][71] Furthermore, investigations have shown that the γ value of two-dimensional macrocycles, such as phthalocyanines, depends on contributions coming from a larger number of components.…”
Section: Cation Sensing Studymentioning
confidence: 99%
“…The band around 468 nm can be ascribed to a MLCT transition of the Cu + complex, and the wide absorption centered at 894 nm can be defined as the charge transfer to ferrocenium. 26,69,74 The changes in the absorption spectra are accompanied by a color change from faint yellow to red, which provides the potential for "naked eye" detection. The red solution was stable at room temperature, due to the strong affinity of the Se donor and Cu + .…”
Section: Cation Sensing Studymentioning
confidence: 99%